2019
DOI: 10.1002/gps.5183
|View full text |Cite
|
Sign up to set email alerts
|

Psychosis of Alzheimer's disease: Neuropsychological and neuroimaging longitudinal study

Abstract: Objectives Psychosis of Alzheimer's disease (AD) may represent a distinct disease phenotype; however, neuropsychological profile and neural basis linked to this phenotype have not yet been clarified. In this study, we aimed at detecting whether impairment in specific cognitive domains predicts the onset of psychosis in AD patients and what grey matter alterations, their location, and the rate of atrophy are associated with psychosis of AD. Methods Longitudinal neuropsychological data from AD patients with and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 45 publications
(97 reference statements)
1
12
1
Order By: Relevance
“…These results suggest that AD psychosis may represent a distinct phenotype that is associated with specific structural alterations, in line with previous studies (Ismail et al, 2012; Y. M. Lee et McLachlan et al, 2018). These results also suggest a pivotal role of the ventral visual stream in AD psychosis, consistent with previous studies from our group (D'Antonio, Di Vita et al, 2019;. Thus, our findings provide additional evidence that structural alterations in functionally specialized visuoperceptual regions may underpin cognitive alterations in the perception and interpretation of visual stimuli, which may contribute to psychosis onset (D'Antonio, Di Vita et al, 2019).…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…These results suggest that AD psychosis may represent a distinct phenotype that is associated with specific structural alterations, in line with previous studies (Ismail et al, 2012; Y. M. Lee et McLachlan et al, 2018). These results also suggest a pivotal role of the ventral visual stream in AD psychosis, consistent with previous studies from our group (D'Antonio, Di Vita et al, 2019;. Thus, our findings provide additional evidence that structural alterations in functionally specialized visuoperceptual regions may underpin cognitive alterations in the perception and interpretation of visual stimuli, which may contribute to psychosis onset (D'Antonio, Di Vita et al, 2019).…”
Section: Discussionsupporting
confidence: 93%
“…Neuroimaging studies have reported that AD patients with psychosis (AD-P) show gray matter (GM) alterations mainly in fronto-temporal regions, as summarized by Ismail and colleagues in their review (Ismail et al, 2012). Recent longitudinal studies have reported that psychosis in AD may be associated with a greater rate of atrophy in fronto-temporal regions and in regions of the inferior temporal lobe and insula, suggesting that the co-occurrence of misperception and misattribution may underpin psychosis in AD (D'Antonio, Di Vita et al, 2019). A study that investigated cortical thickness in AD psychosis reported that AD-P patients have a greater reduction in bilateral hippocampal volume than AD patients without psychosis (K. Lee et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…OADWS can experience periods of agitation in long-term care facilities, generated in part by cognitive confusion and labile mood (APA, 2013; NIMH, 2018). Many OADWS experience psychosis, a condition that can be related to schizophrenia or other comorbid diagnoses such as Alzheimer's disease (Connors et al, 2018; D’Antonio et al, 2019; Reeves et al, 2017; Roberton & Daffern, 2020). Although OADWS have human agency and may express agitation , they are also bound by the social constraints of long-term care facilities, which require their protection as well as the protection of others with whom they live.…”
Section: Holistic Principles Of Nursing With An Lct Lensmentioning
confidence: 99%
“…8, the escape rate of module 1 is the smallest among the three types of data, so we choose module 1 for further analysis. [24], Angular Gyrus [25], Fusiform Gyrus [26], Inferior Occipital Gyrus [27], Inferior Temporal Gyrus [28], Lingual Gyrus [29], Middle Frontal Gyrus [30], Middle Temporal Gyrus [31], Precuneus [32], Postcentral Gyrus [33], Precentral Gyrus [34], Supramarginal Gyrus [35], Superior Parietal Lobule [36], Superior Temporal Gyrus [37] have been confirmed to be risk brain regions for AD. Also, we identify a total of 47 risk genes from the SNPs data in the first module.…”
Section: Results On Adni Databasementioning
confidence: 99%